Are Purchase Decisions Influenced by Halal Labeling and Brand Awareness? Evidence from Wardah Cosmetics - Jannatul (Nusantara Journal of Multidisciplinary Science, 2024)
For most women, one of their most fundamental needs is cosmetics. Wardah is one of the halal cosmetic brands available in Indonesia. The aim of this research is to determine whether brand recognition and the halal label influence the purchasing decisions of Wardah products partially and simultaneously. Researchers utilize quantitative research with a descriptive research design and SPSS 25 to address this issue. Purchase decision (Y) is the dependent variable in this study, while brand awareness (X2) and halal labeling (X1) are independent variables. Customers who have the option to purchase Wardah products constitute the demographic under study. Following the Pao Purba formula, 100 sources are utilized to calculate the sample size for this research, resulting in a sample of 100 respondents. Participants will provide responses on a five-point Likert scale ranging from strongly disagree, disagree, neutral, agree, to strongly agree, used in this study. Subsequently, validity and reliability tests will be employed to assess the instrument's suitability. Tests for multicollinearity, heteroskedasticity, and normality are used in testing classical assumptions. T-tests, F-tests, and R-square are used in hypothesis testing. The research findings indicate that brand awareness and halal certification, both partially and simultaneously, influence consumers' purchasing decisions of Wardah products.